4n=m(5-n)

Simple and best practice solution for 4n=m(5-n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n=m(5-n) equation:


Simplifying
4n = m(5 + -1n)
4n = (5 * m + -1n * m)
4n = (5m + -1mn)

Solving
4n = 5m + -1mn

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'mn' to each side of the equation.
mn + 4n = 5m + -1mn + mn

Combine like terms: -1mn + mn = 0
mn + 4n = 5m + 0
mn + 4n = 5m

Reorder the terms:
-5m + mn + 4n = 5m + -5m

Combine like terms: 5m + -5m = 0
-5m + mn + 4n = 0

The solution to this equation could not be determined.

See similar equations:

| 3x^2-10x-28=0 | | -x^2+14x-57=0 | | -10=30 | | 64=2a+a^2+1 | | 2x^3+x^2-4x-3=0 | | x+4=2(.4x+1.3) | | 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) | | 5x-13=4(2x-5) | | 5b+6-6b+2= | | 9x^2-32=40 | | 5.5q-4.6-6.6q=2.2-1.1q-2.4 | | 6.1x+3=5.1x | | 10(-2x+1)=-12(x+2)+34-8x | | 7x+9-8x+4=6x-7x-5 | | 7x+3=3+7x | | 7x+4y=18.25 | | 4(7x-2)+5(19-3x)=3(4x+3)-6 | | 2y+110+35=180 | | 5a+7=3a-15 | | 18x+4=58 | | (6x+7)-(4+5x)=12 | | (4*2k)+3k-2= | | 9+10r-2=9r+35-3r | | 48x^2+24x+3=0 | | x=-60+2s | | 2y+110+35=360 |

Equations solver categories